2014
DOI: 10.1111/cts.12152
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Antioxidants and Lung Function in Asthmatics during High Ozone Season: A Closer Look at Albumin, Glutathione, and Associations with Lung Function

Abstract: Background: Asthma is a chronic airway inflammatory disease with episodic symptoms of wheezing, chest tightness, cough, and shortness of breath. High ambient ozone levels have been associated with increased airway inflammation and asthma morbidity in prior studies. Mechanisms underlying individual susceptibility to asthma exacerbations from poor air quality are not fully understood. Objective: As part of a panel observational study, we hypothesized that systemic antioxidant ability and antioxidant status may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…Therefore, we hypothesized that albumin is an indicator of inflammatory process, and for this reason it is related with poor pulmonary function 20 . Khatri et al 13 showed that plasma albumin levels directly correlated with FEV 1 % predicted among asthmatic subjects (R=0.378; p=0.010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we hypothesized that albumin is an indicator of inflammatory process, and for this reason it is related with poor pulmonary function 20 . Khatri et al 13 showed that plasma albumin levels directly correlated with FEV 1 % predicted among asthmatic subjects (R=0.378; p=0.010).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Khatri et al 13 observed that albumin was significantly correlated with lung function and asthma quality of life scores. There is only one study that demonstrated albumin as a predictor of lung function in CF subjects 14 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Air pollution has been associated with poor health outcomes and continues to be a risk factor for respiratory health. Epidemiologic, panel, and longitudinal cohort studies in adults and children have demonstrated increased frequency of asthma symptoms, new onset of asthma, worsening of lung function, reduced pace of lung development, and increased airway inflammation, including from oxidant stress [ 1 4 ]. During times of poor air quality with higher levels of air pollution, the deleterious effects are evident by acute and chronic symptomatology and development of chronic diseases, such as allergic rhinitis and asthma [ 5 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under pathological conditions, the highly expressed VEGF binding to its receptor can cause structural changes in the extravascular matrix and interstitial oedema, cause airway remodelling and aggravate asthma symptoms (Zhao et al, 2018). (Khatri et al (2014). found that albumin significantly correlated with lung function (%FEV(1)) and asthma quality of life scores.…”
mentioning
confidence: 99%